Preparation and characterization of sorbitol modified nanoclay with high amylose bionanocomposites - Liu, Huihua; Chaudhary, Deeptangshu; Yusa, S.; Tade, Moses (Elsevier, 2011)
We investigate the influence of sorbitol and natural Na+-montmorillonite (nanoclay) loading on the characteristic of high amylose nanocomposites and the distribution of nanoclay after extrusion processing. The innovative aspect is the modification of the nanoclay using the sorbitol plasticizer, and as shown in the XRD results, good intercalated/exfoliated morphology had been achieved in all nanocomposites. The expansion of nanoclay gallery relates to sorbitol loading and nanoclay concentration. Evidence of newly formed hydrogen bonds, due to plasticizer and nanoclay interaction, and also the ternary interaction among starch/sorbitol/nanoclay were taken from peaks associated with –OH stretching located at 3300cm−1 and 999cm−1 from the FTIR spectra. Further, 13C NMR spectra demonstrated that the sorbitol mobility was significantly lowered with 1% nanoclay and overall, sorbitol mobility was lower than that of starch chains. TEM directly supported the presence of exfoliated and intercalated/exfoliated morphologies. Furthermore, calorimetric analysis revealed that the glass transition temperature (Tg) decreased with increasing sorbitol content and the presence of nanoclay improved the thermal stability and crystallinity of corresponding samples.